(untitled) (Annual of the Faculty of Philosophy in Skopje, 2018)
The overall aim of this study was to explore the relationships among self-ob- jectification and gender identity in young women and men. Two self-objectification aspects (body surveillance and body shame), exercise activity and time spent in “beautifying” were investigated in relation to sex, gender identity. A sample of340 ethnic Macedonians (50% male) at average age of M=25.21 years (SD=5.60) participated in the study by providing background information (including self-assessed time spent in physical activity and beautifying) and fulfilling two subscales of the Objectified Body Consciousness Scale (McKinley & Hyde, 1996) and Femininity/Masculinity trait index scale (Barak & Stern, 1986). The three hypotheses were tested by using two-way AN OVA and correlation coefficients and all of them were partially confirmed. The author concludes that women tend to self-objectify themselves more than men and that this tendency is in interaction with the extent to which one identifies her/himself with the gender role. In addition, results suggest that self-objectification is connected to different health-related behaviour of women and men.